2017
DOI: 10.1177/0884533617692774
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Outcome‐Based Approaches to Protein Requirements in the Intensive Care Unit

Abstract: Insight into protein requirements of intensive care unit (ICU) patients is urgently needed, but at present, it is unrealistic to define protein requirements for different diagnostic groups of critical illness or at different stages of illness. No large randomized controlled trials have randomized protein delivery, adequately addressed energy intake, and evaluated relevant clinical outcomes. As a pragmatic approach, experimental studies have focused on protein requirements of heterogeneous ICU patients. Data ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…Delivery of energy above and below an individual's needs may be detrimental to muscle mass. Specifically, caloric restriction can lead to protein‐energy malnutrition and muscle wasting, while overfeeding energy may decrease capillary blood flow and amino acid transfer to muscle tissue via perivascular adipose tissue . The majority of participants in this review received appropriate energy provision for the acute stages of critical illness compared with measured needs or clinical guidelines .…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of energy above and below an individual's needs may be detrimental to muscle mass. Specifically, caloric restriction can lead to protein‐energy malnutrition and muscle wasting, while overfeeding energy may decrease capillary blood flow and amino acid transfer to muscle tissue via perivascular adipose tissue . The majority of participants in this review received appropriate energy provision for the acute stages of critical illness compared with measured needs or clinical guidelines .…”
Section: Discussionmentioning
confidence: 99%
“… 77 The basis for the protein dose recommendation includes a number of studies with nitrogen balance as the outcome. 79 As an example, Ishibashi et al 80 tested three protein intake levels (1.1, 1.5, and 1.9 g/kg of FFM) and found that a median protein intake of 1.5 g/kg/FFM or 1.2 g/kg or actual body weight was associated with the lowest body protein loss. Similarly, multiple observational studies have suggested that a protein target of >1.2 g/kg of body weight was associated with lower mortality, even when independent of caloric goal.…”
Section: How To Provide Tube Feedingmentioning
confidence: 99%
“…Consideration should also be placed on N balance interpretation when providing insight to inform protein provision. For instance, are clinical outcomes similarly affected with an N balance of −17 g/d improving to −12 g/d compared with −7 g/d improving to −2 g/d, or is there a certain N balance threshold that needs to be met to prove beneficial?…”
Section: Protein Requirementsmentioning
confidence: 99%
“…Although flaws in current protein dosing guidelines are easily identified, it is difficult to propose new recommendations capable of maintaining muscle mass because of the complexity of an individual's response to protein intake. Many factors are capable of altering the body's ability to convert dietary protein into cellular protein, including protein quality (ie, dietary protein amino acid composition and digestibility), digestion rate, nonprotein energy intake, anabolic resistance, muscle disuse, timing of ingestion, and inflammatory status . The sum of these factors make defining protein requirements for a clinical population very difficult.…”
Section: Difficulties Determining Requirementmentioning
confidence: 99%
See 1 more Smart Citation